A liver lesion in primary sclerosing cholangitis. (31st March 2015) - Biswas, Sujata; Rajoriya, Neil; Wang, Lai Mun; Collier, Jane
Abstract : Primary sclerosing cholangitis is associated with an increased risk of cholangiocarcinoma; appropriate surveillance should be undertaken for this. Our case illustrates an unexpected liver lesion in such a patient, which would not have been detected with imaging alone. In suspected cancer, if a patient is not a candidate for liver resection, liver biopsy should be considered in case there is a treatment option for an alternative cause of the liver lesion. This is a careful decision to be made due to the risk of tumour seeding compromising cure and needs to be discussed via the hepatobiliary multidisciplinary team.